Volume 2B: Turbomachinery 2017
DOI: 10.1115/gt2017-63959
|View full text |Cite
|
Sign up to set email alerts
|

The Aerodynamic Design of the Low Pressure Air Delivery Ducts for a Cooled Cooling Air System

Abstract: As aero gas turbines strive for higher efficiencies and reduced fuel burn, the trend is for engine overall pressure ratio to increase. This means that engine cycle temperatures will increase and that cooling of various engine components, for example the high pressure turbine, is becoming more difficult. One solution is to employ a cooled cooling air system where some of the compressor efflux is diverted for additional cooling in a heat exchanger fed by air sourced from the by-pass duct. Design of the ducting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It will be shown in the next sub-section that nine input variables are needed to geometrically determine this problem. A full factorial of the nine inputs would perhaps be computationally viable if sampling was limited to two levels per input variable (i.e., 2 9 = 512 iterations). However, as mentioned above, more levels are required to directly observe the highly nonlinear effects in this study.…”
Section: Design Space Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It will be shown in the next sub-section that nine input variables are needed to geometrically determine this problem. A full factorial of the nine inputs would perhaps be computationally viable if sampling was limited to two levels per input variable (i.e., 2 9 = 512 iterations). However, as mentioned above, more levels are required to directly observe the highly nonlinear effects in this study.…”
Section: Design Space Reductionmentioning
confidence: 99%
“…However, as mentioned above, more levels are required to directly observe the highly nonlinear effects in this study. Even as few as three levels are not computationally affordable (i.e., 3 9 2 × 10 4 iterations). Preliminary sampling of the design space showed that not all input variables interact strongly to one another and suggested that reduction of this full factorial into three fractions is possible without risking the elimination of high value design families.…”
Section: Design Space Reductionmentioning
confidence: 99%
See 3 more Smart Citations